2013
DOI: 10.1371/journal.pone.0050492
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and Public Health Cost of a Statewide Influenza Nurse Triage Line in Response to Pandemic H1N1 Influenza

Abstract: BackgroundThe 2009 H1N1 pandemic strained healthcare systems. There was a need for supportive services, rapid antiviral access, and minimization of unnecessary healthcare contacts particularly face-to-face interactions. In response, the Minnesota Department of Health (MDH) launched a telephone-based nurse triage line (NTL) called the Minnesota FluLine coordinating all major MN healthcare systems with NTLs to form a single toll-free number triage service. Callers were evaluated for symptoms of influenza-like il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Cost per call was found to be $268, which is higher when compared with findings of other studies of telephone triage services. 8,10,30,31 About 80% of all ED presentations from RACFs were not associated with prior ACE calls ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost per call was found to be $268, which is higher when compared with findings of other studies of telephone triage services. 8,10,30,31 About 80% of all ED presentations from RACFs were not associated with prior ACE calls ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study identified savings from ACE, the cost per phone call of A$268 is relatively high when compared with those found in other studies. 8,10,30,31 However, as pointed out by Cullen and Wilson, cost-effectiveness is usually achieved in telephone triage services with large scale operations; they found that the average cost per call for six general practice triage services was A$162, 30 whereas the Western Australia Health Call Centre telephone triage service had a per-call cost of A$23. 32 The ACE program receives a relatively small number of calls compared with major triage services for general populations.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 An important theme voiced by participants across all sessions relates to using several simultaneous strategies-a ''layered'' approach-to facilitate access to antivirals. Participants recognized that no single strategy can solve the full range of problems that might emerge during a severe pandemic.…”
Section: Access To Antivirals In An Influenza Pandemicmentioning
confidence: 99%
“…25 They could foresee the potential limitations of each strategy-for instance, the possibility that telephone triage lines could become overwhelmed, a situation that Minnesota's FluLine had to address during the H1N1 pandemic. 23 Yet, they understood that several of these strategies combined could enhance their efficacy. This realization may have been responsible for the high overall acceptability of the alternative strategies despite the noted deficiencies of each.…”
Section: Access To Antivirals In An Influenza Pandemicmentioning
confidence: 99%
“…During the 2009 H1N1 pandemic, nurse triage lines reduced in-person visits for influenza-like symptoms, were cost effective, had a high degree of satisfaction among callers, and were able to reach rural and uninsured populations. [4,5,6,7] Reaching vulnerable populations and those of lower socioeconomic status (SES) during a pandemic is of particular importance as individuals of lower SES have greater barriers to information access and are more likely to adopt incorrect protective behaviors. [8] To further promote telehealth in the COVID-19 era, throughout March and April of 2020 federal and state policies have been altered to remove or ease geographic restrictions and other regulatory barriers to telehealth visits.…”
Section: Introductionmentioning
confidence: 99%